The effects of infant abdominal massage on the parental stress level among Chinese parents in Hong Kong - A mixed clustered RCT - Veronica S. K. Lai; Daniel Y. T. Fong (BMC, 2024)
Abstract Objective To investigate the effectiveness and the experience of infant abdominal massage on reducing the parental stress level. Methods A clustered RCT was conducted, 160 parents were recruited from 10 mother groups. An infant abdominal massage class was given to those in the intervention group by a certified International Association of Infant Massage instructor. The Chinese Parenting Stress Index (PSI-SF) was used to measure parental stress levels at baseline and 4 weeks after the intervention. 8 parents from the intervention group were invited for an online interview to understand the experience of parents in participating the infant abdominal massage class. Thematic analysis was applied. Results The parental stress level was significantly decreased among intervention group with a mean difference of -5.46 (95% CI = 0.72 to 10.2, p = .049). ITT analysis was adopted for compliance analysis. The overall compliance for the intervention was 66% and found to have a significant effect on parental stress level (p < .01). The total PSI-SF among fathers was slightly higher than that among mothers. Furthermore, no moderating factors were found to have a significant interaction effect on PSI-SF (p < .05).For qualitative data, an overarching theme was generated that infant abdominal massage brought a positive experience despite the uncertainties affecting the compliance. Four themes and nine sub-themes were identified. Which were: (1) receiving clear and informative infant abdominal massage classes; (2) The influence of uncertain conditions on compliance; (3) Improving parental satisfaction; and (4) feeling it was a worthwhile experience. Conclusion This study provides a cost-effective method for parents to tackle their parental stress, the findings aid in the planning or adjustment of current postpartum depression screening while also helping to lower the risk of postpartum mood disorders. Trial registration Clinical Trial Number (NCT05650424 || http://clinicaltrials.gov/study/NCT05650424 ), registered on December 1, 2022. and HKU Clinical Trails Registry (HKUCTR3008), registered on November 3, 2022.